2015
DOI: 10.1111/vru.12238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Elastography of the Liver, Spleen, Kidneys, and Prostate in Clinically Normal Beagle Dogs

Abstract: Standard ultrasonography is often insensitive for distinguishing normal vs. diseased states for canine abdominal organs. Ultrasonographic elastography is a new technique that is becoming increasingly available and may help to improve sensitivity. This study evaluated the feasibility, repeatability, and reproducibility of strain elastography of the liver, spleen, kidneys, and prostate in healthy dogs and described the elasticity of each organ using strain values and strain ratios. The reproducibility of strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 34 publications
9
40
0
1
Order By: Relevance
“…Considering the strain ratio between the stiffness of the spleen and the stiffness of the abdominal wall, the inter-and intraobserver variability of strain elastography have already been demonstrated (Jeon et al, 2015). Our study showed the repeata- of compression and retraction of the probe as equal as possible between them.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Considering the strain ratio between the stiffness of the spleen and the stiffness of the abdominal wall, the inter-and intraobserver variability of strain elastography have already been demonstrated (Jeon et al, 2015). Our study showed the repeata- of compression and retraction of the probe as equal as possible between them.…”
Section: Discussionsupporting
confidence: 65%
“…In human medicine, malignant parenchymal lesions are significantly stiffer than surrounding normal parenchyma (Wells & Liang, 2011;Barr, 2012;Teng et al, 2012;Wang et al, 2013). Strain elastography has proven to be a feasible technique for estimating tissue stiffness in the healthy canine liver, spleen, kidneys and prostate (Jeon et al, 2015). To our knowledge there are no studies concerning the evaluation of splenic lesions using real time elastosonography neither in humans nor in small animal medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The manual compression elastography and ARFI techniques were related for evaluating canine splenic stiff ness (Holdsworth et al, 2014;Jeon et al, 2015;Maronezi et al, 2015b). Qualitative evaluation reported by Jeon et al (2015) was performed on the colour elastogram and the calculated splenic strain intensity was compared with abdominal wall strain intensity, resulting in the splenic strain rate that may be useful for normal and abnormal spleen evaluation.…”
Section: Elastographymentioning
confidence: 99%
“…Qualitative evaluation reported by Jeon et al (2015) was performed on the colour elastogram and the calculated splenic strain intensity was compared with abdominal wall strain intensity, resulting in the splenic strain rate that may be useful for normal and abnormal spleen evaluation. A preliminary study published by Holdsworth et al (2014) determined the quantitative elastographic characteristics of the normal liver, spleen, and kidneys in 15 healthy dogs at predetermined depths within the parenchyma.…”
Section: Elastographymentioning
confidence: 99%
“…Özellikle fibrozisin yaygın olduğu durumlarda biyopsi ile eksik ve yanlış örnek alınabileceği için daha avantajlı olabilmektedir. Meme, tiroid ve prostat kanserlerinin belirlenmesinde kullanılabilir (11)(12)(13). Yine bazı özel elastografi cihazları kas ve tendon yapısını değerlendirebilmekte ve bu dokuların mekanik özelliklerinin belirlenmesinde yararlı olmaktadır (14).…”
Section: Elastografi Uygulamalarıunclassified